2018
DOI: 10.30984/ajip.v3i1.636
|View full text |Cite
|
Sign up to set email alerts
|

Metode Pendidikan Kajian Agama Di Universitas: Sebuah Alternatif

Abstract: Abstract. This paper offers “Religous Studies” approach as an alternative in religious education within universities in Indonesia that emphasized discussing religions from the various perspective of social sciences. Goals of this approach are preparing students to have more diverse knowledge on religions not limited on his or her own belief, encouraging dialogue between people of different religious beliefs, sharing spiritual experiences and engaging in religious pluralism. This approach is applied in a class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Syarif (Syarif, 2018) mengemukakan bahwa bahwa pandangan dan sikap ilmiah yang menjadi ciri khas masyarakat intelektual di dunia akademik mengalami kemerosotan ketika dogmatisme agama yang bersifat eksklusif merasuki insan akademis hal ini ditandai dengan beberapa temuan terakhir mengenai meningkatnya geliat dakwah kampus melalui berbagai macam organisasi serta kegiatan kemahasiswaan baik yang bersifat intra maupun ekstra kampus. Sebagai contoh adalah laporan penelitian LPPM Unusia, Kelompok Islam yang bergerak secara eksklusif berkembang pesat di delapan perguruan tinggi negeri (PTN) (Isnanto, 2019).…”
Section: Pendahuluanunclassified
“…Syarif (Syarif, 2018) mengemukakan bahwa bahwa pandangan dan sikap ilmiah yang menjadi ciri khas masyarakat intelektual di dunia akademik mengalami kemerosotan ketika dogmatisme agama yang bersifat eksklusif merasuki insan akademis hal ini ditandai dengan beberapa temuan terakhir mengenai meningkatnya geliat dakwah kampus melalui berbagai macam organisasi serta kegiatan kemahasiswaan baik yang bersifat intra maupun ekstra kampus. Sebagai contoh adalah laporan penelitian LPPM Unusia, Kelompok Islam yang bergerak secara eksklusif berkembang pesat di delapan perguruan tinggi negeri (PTN) (Isnanto, 2019).…”
Section: Pendahuluanunclassified
“…Moreover, this Islamic fundamentalist thought has strengthened up and entered into the system of state universities. Various researches showed that public state universities in Indonesia such as UGM (Gadjah Mada University, ITB (Bandung Technological Institute), UI (the University of Indonesia), and other state universities in a rural area such as UNILA (Lampung University) of which type of religious activities are managed by a group of Islamic fundamentalist (Syarif & Mantu, 2018;Zein, 2012) encouraging dialogue between people of different religious beliefs, sharing spiritual experiences and engaging in religious pluralism. This approach is applied in a class that is attended by students whatever religious affiliations.…”
mentioning
confidence: 99%